The impact of moral harassment (mobbing) on the job satisfaction of the medical and nursing staff of the two major hospitals in Patras, Greece - Felekis, Achillefs; Theodorou, Panagiotis; Intas, George; Flokou, Angeliki (International Conference on Business and Economics - Hellenic Open University, 2025)
The study investigates ethical harassment and its impact on job satisfaction among healthcare professionals in two large hospitals in Patras. Conducted from January to March 2024, the research utilized an anonymous, structured questionnaire. The LIPT (Leymann Inventory of Psychological Terror) assessed workplace harassment, while the KUHJSS (Kuopio University Hospital Job Satisfaction Scale) evaluated job satisfaction. Out of 220 professionals (physicians and nurses) approached, 180 (82%) responded. Results showed that 44.4% of respondents experienced moral harassment within the last 12 months, with 96% reporting psychological violence. Additionally, 63.3% witnessed psychological violence against colleagues. Among those harassed, 25% encountered it weekly, and 15% nearly daily, with 55.8% still facing harassment. Supervisors or higher-level employees were the main sources of harassment (58.9%), and 33.3% of incidents involved women. Notably, 41.7% of victims discussed the incidents with colleagues. In terms of job satisfaction, healthcare professionals were more content with motivation, leadership, and team spirit, but less satisfied with their work environment. Additionally, those who had not experienced moral harassment in the past 12 months reported higher satisfaction with their work environment compared to those who had been harassed. Secondary school graduates were more likely to have experienced moral harassment in the past 12 months than those with a master's or doctoral degree. Finally, nurses reported experiencing psychological harassment more frequently over the past year compared to doctors. The high prevalence of moral harassment and its negative impact on job satisfaction highlight the urgent need for hospital management to implement preventive measures and foster a supportive work environment. JEL Classifications: I19, M12, M14 Keywords: Moral Harassment, Psychological Violence, Nursing Staff, Job Satisfaction